2015
DOI: 10.1007/s00253-015-6530-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of reuterin from glycerol by magnetically immobilized Lactobacillus reuteri

Abstract: Reuterin is a compound that contains the monomeric, hydrated monomeric, and cyclic dimeric forms of 3-hydroxypropionaldehyde (3-HPA). It is widely used as a food preservative due to its antimicrobial properties, and 3-HPA is also an important precursor for several industrial chemicals. In this study, we first developed an efficient immobilization process involving magnetic cell entrapment for production of reuterin from glycerol by Lactobacillus reuteri. The cell growth condition was optimized by statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…LAB possess specific characteristics, including small genome sizes, high sugar uptake, high tolerance to environmental stress, and uncoupled growth and energy metabolism. Such features render them natural cell factories for industrial production of metabolites and enzymes [ [182] , [183] , [184] , [185] ].…”
Section: Applications Of Crispr-cas9/cas12a Biotechnology In Bacteriamentioning
confidence: 99%
“…LAB possess specific characteristics, including small genome sizes, high sugar uptake, high tolerance to environmental stress, and uncoupled growth and energy metabolism. Such features render them natural cell factories for industrial production of metabolites and enzymes [ [182] , [183] , [184] , [185] ].…”
Section: Applications Of Crispr-cas9/cas12a Biotechnology In Bacteriamentioning
confidence: 99%
“…With the increase of Fe 3 O 4 NPs, the biodegradation rate by immobilized cells was increased accordingly till to the Fe 3 O 4 NPs concentration of 9 g/L. These results revealed that the biodegradation activity of the immobilized R. rhodochrous DSM6263 cells was significantly enhanced by adding Fe 3 O 4 NPs, which should be beneficial to the reduced mass transfer resistance and the accelerated material transportation as compared to the traditional immobilization methods [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For preparation of magnetically immobilized cells, Fe 3 O 4 nanoparticles (NPs) suspension was added to the above dissolved k -carrageenan with the same amount of cell suspension, and solidified in the same procedure [ 13 ]. The Fe 3 O 4 NPs were prepared by the modified coprecipitation method as previous report [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an intermediate in the metabolism of glycerol to 1,3-propanediol catalyzed by the coenzyme B12-dependent diol dehydrase (oxygen-sensitive and membrane-associated glycerol dehydratase). If not released, 3-HPA is reduced by the (NADH)+H+-dependent-1,3-propanediol-oxydoreductase regenerating NAD+ [21][22][23]. The production is rate-limited because, if overproduced, reuterin is toxic for the producer cell [21].…”
Section: Introductionmentioning
confidence: 99%